Gold Nanostructures on Self-Assembled Monolayers Activity for Epinephrine, Noradrenaline and Dopamine - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Rojas, J; Silva-Rojas, J; Silva-Gonzalez, N; Silva-Gonzalez, N; Oyarzun-Medina, M; Oyarzun-Medina, M; Ramírez-Pastén, S; Ramírez-Pastén, S (Elsevier B.V., 2017)
The incorporation and effective containment of gold nanostructures on a substrate electrode applied to electrochemical sensors for detecting neurotransmitters is studied. Gold nanoparticles (AuNPs) and gold nanorods (AuNRs) were synthesized, and these nanostructures were incorporated into a metal substrate mediated by self-assembled monolayers (SAMs) of 4-mercaptopyridine (4MPy), which allows the effective confinement and communication of the nanostructure, in addition to evaluating the anisotropic effect for the oxidation of neurotransmitters. Characterizations were made to corroborate the constructed system. First, the nanostructures synthesized in solution were characterized by UV–visible spectroscopy and transmission electron microscopy (TEM). Second, the systems were characterized both chemically and morphologically. Third, an electrochemical characterization was performed as working electrodes. Finally, it was studied by cyclic voltammetry detection of neurotransmitters, for the device formed with AuNRs obtained a better electrochemical response than the system consisting of the AuNPs. Additionally, a shift of the peak oxidation potential of the neurotransmitters used took place depending on the nanostructure observed. Therefore, the oxidation potential of the neurotransmitter depends on the anisotropy of the nanostructure. © 2017 Elsevier B.V.